Beyond Opportunity Costs: Campaign Messages, Anger and Turnout among the Unemployed. Issue 4 (29th October 2020) - Aytaç, S. Erdem; Rau, Eli Gavin; Stokes, Susan
Abstract: Are people under economic stress more or less likely to vote, and why? With large observational datasets and a survey experiment involving unemployed Americans, we show that unemployment depresses participation. But it does so more powerfully when the unemployment rate is low, less powerfully when it is high. Whereas earlier studies have explained lower turnout among the unemployed by stressing the especially high opportunity costs these would-be voters face, our evidence points to the psychological effects of unemployment and of campaign messages about it. When unemployment is high, challengers have an incentive to blame the incumbent, thus eliciting anger among the unemployed. Psychologists have shown anger to be an approach or mobilizing emotion. When joblessness is low, campaigns tend to ignore it. The jobless thus remain in states of depression and self-blame, which are demobilizing emotions.